2016
DOI: 10.3389/fnhum.2016.00595
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Limitations of Computer Gesture Therapy for the Rehabilitation of Severe Aphasia

Abstract: Aphasia intervention has made increasing use of technology in recent years. The evidence base, which is largely limited to the investigation of spoken language outcomes, indicates positive treatment effects for people with mild to moderate levels of aphasia. Outcomes for those with severe aphasia, however, are less well documented and – where reported – present less consistent gains for measures of spoken output. This study investigates the effects of a purpose-built gesture therapy technology for people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Specifically, both explicit learning [22,24,3942], working memory and attention [4345], and the generation of voluntary saccades [4650] depend on contributions from a ‘dorsal attention network’ [45] of (pre)frontal-parietal regions (most notably the frontal eye fields and dorsolateral prefrontal cortex). Although the neural site of adaptation (rather than generation) of reactive and scanning saccades remains an active area of investigation [3,5154], a recent study suggested that the adaptation of voluntary compared to reactive saccades places larger demands on the dorsal- compared to the ventral attention network [55]. In sum, this suggests that the demand for cognitive resources required by both voluntary saccades and explicit learning can be viewed in terms of competition for neural resources, most likely in the dorsal attention network.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, both explicit learning [22,24,3942], working memory and attention [4345], and the generation of voluntary saccades [4650] depend on contributions from a ‘dorsal attention network’ [45] of (pre)frontal-parietal regions (most notably the frontal eye fields and dorsolateral prefrontal cortex). Although the neural site of adaptation (rather than generation) of reactive and scanning saccades remains an active area of investigation [3,5154], a recent study suggested that the adaptation of voluntary compared to reactive saccades places larger demands on the dorsal- compared to the ventral attention network [55]. In sum, this suggests that the demand for cognitive resources required by both voluntary saccades and explicit learning can be viewed in terms of competition for neural resources, most likely in the dorsal attention network.…”
Section: Discussionmentioning
confidence: 99%
“…Other work seeks to support more practical activities such as cooking [45]. Accessible digital technologies have also enabled rehabilitative therapy for improving gestures [41] and spoken language [16,26]. Contrasting work has sought to classify aphasic language input computationally [15].…”
Section: Aphasia and Content Creationmentioning
confidence: 99%
“…I have worked with lots of people who have aphasia using technology. With demonstration and practice, they have all been able to achieve some level of independent use of specifically-designed therapy technology [8,11,12]. However, many of them report that they cannot achieve this level of access to mainstream technologies -even for technologies that they were highly skilled at using prior to the onset of their aphasia.…”
Section: Question 2 How Does Your Aphasia Affect the Way People Use mentioning
confidence: 99%